Application of Standard Processes in Class Visit Supervision to Improve Teacher Performance in Sdn 34 Saning Bakar - Eidmondi Eidmondi; Farida F; Darmansyah Darmansyah (Postgraduate School, Universitas Negeri Padang, 2019)
This research takes the form of school action research (PTS), which is the improvement of teacher performance with class visit techniques in order to implement standard processes, which consist of 2 cycles and each cycle consists of 4 stages: (1) action program planning stage, (2 ) implementation of action programs, (3) program observations, (4) reflection. Based on the research that has been done, it can be summarized as follows: Application of Class Visit supervision at SDN 34 Saning Bakar following the procedure based on the opinion of Sahertian (2000: 106) which is divided into four main steps namely: (1) planning (2) implementation and observation, (3) reflection There is an increase in the ability of class teachers at SDN 34 Saning Bakar after the implementation of supervision of class visits which initially only 30.17, in the first cycle rose to 40.17, in the second cycle to 57.17 and in silus III to 74, 50. There was an increase in the ability to carry out classroom teacher learning at SDN 34 Saning Bakar after the implementation of class visit supervision from the initial value of 29.73, in the first cycle rose to 44.33 in the second cycle rose to 55.33 and in the third cycle to 77.67.